2017
DOI: 10.2139/ssrn.3053569
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Using Films in the EFL Classroom: A Case Study Conducted at an International University in Thailand

Abstract: Films have always been seen as an entertainment and its power since birth has had strong impact on people's lives. Today, films are no longer thought of as simple entertainment media but rather educational tools as well. Globalization has contributed greatly to the availability of English-language films and that enriches the source of English learning material dramatically. This research paper explores the effect of using English films in English as foreign language (EFL) classroom. It reveals the effect on de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…This is consistent with previous studies (e.g. Kabooha, 2016;Kalra, 2017;Liando et al, 2018;Pamungkas & Adi, 2020) that suggested the exposure to authentic language could positively affect the improvement of listening skills. Moreover, the findings showed that the visual effects of English films also had a moderate positive correlation with listening comprehension.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This is consistent with previous studies (e.g. Kabooha, 2016;Kalra, 2017;Liando et al, 2018;Pamungkas & Adi, 2020) that suggested the exposure to authentic language could positively affect the improvement of listening skills. Moreover, the findings showed that the visual effects of English films also had a moderate positive correlation with listening comprehension.…”
Section: Discussionsupporting
confidence: 93%
“…Albiladi et al, 2018;Goctu, 2017) that reported similar benefits of English films for language acquisition. Likewise, Kabooha (2016) and Kalra (2017) who investigated the integration of films in lesson confirmed that the films facilitated the English language learning.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Movies also offer a visual context aid which helps students understand and improve their learning skills" (Goctu, 2017, p121). Another study conducted by Kalra (2017) revealed that "using films in the classroom can be one of the most powerful instructional media which help in developing students' language skills. The participants, both students and teachers, have positive attitudes in incorporating films in their classrooms to improve English skills" (Kalra, 2017, p299).…”
Section: Introductionmentioning
confidence: 99%